2020
DOI: 10.2174/1570163816666190823135948
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol as a Potential PAK4 Inhibitor in Triple Negative Breast Cancer: Extra Precision Glide Docking and Free Energy Calculation

Abstract: Background: P-21 activating kinase 4 (PAK4) is implicated in poor prognosis of many human tumors, particularly in triple negative breast cancer (TNBC) progression. Studies have revealed the crucial role of PAK4 in cell proliferation, anchorage-independent growth and cell migration among other hallmarks of cancer. Thus, PAK4 is an attractive target for anti-TNBC drug design and development. In our research, we used in silico methods to investigate the inhibitory potentials of kaempferol against PAK4 as compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Beta-sitosterol can promote the apoptosis of breast cancer cells by activating the Fas signaling pathway and caspase-8 activity [ 32 ] and is expected to be an orphan nutrition drug against cancer [ 33 ]. Kaempferol has shown a good affinity for PAK4 in molecular docking and is considered to be a potential inhibitor in triple-negative breast cancer [ 34 ], and kaempferol can prevent G2/M phase of the cell cycle by downregulating CDK1 in human breast cancer MDA-MB-453 cells [ 35 ], and blocking RhoA and Rac1 signaling pathways to inhibit breast cancer cell migration and invasion [ 36 ] is a powerful antioxidant inducer and can inhibit oncogene transformation and induce cancer cell apoptosis and DNA damage. Quercetin, naringenin, and isorhamnetin, such as flavonoids, can prevent breast cancer cell migration through inflammatory and apoptotic cell signaling [ 37 , 38 ], and quercetin can induce autophagy by inhibiting the Akt-mTOR pathway [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beta-sitosterol can promote the apoptosis of breast cancer cells by activating the Fas signaling pathway and caspase-8 activity [ 32 ] and is expected to be an orphan nutrition drug against cancer [ 33 ]. Kaempferol has shown a good affinity for PAK4 in molecular docking and is considered to be a potential inhibitor in triple-negative breast cancer [ 34 ], and kaempferol can prevent G2/M phase of the cell cycle by downregulating CDK1 in human breast cancer MDA-MB-453 cells [ 35 ], and blocking RhoA and Rac1 signaling pathways to inhibit breast cancer cell migration and invasion [ 36 ] is a powerful antioxidant inducer and can inhibit oncogene transformation and induce cancer cell apoptosis and DNA damage. Quercetin, naringenin, and isorhamnetin, such as flavonoids, can prevent breast cancer cell migration through inflammatory and apoptotic cell signaling [ 37 , 38 ], and quercetin can induce autophagy by inhibiting the Akt-mTOR pathway [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that these potential active components exhibit antitumor effects. Kaempferol inhibits breast cancer cell proliferation, induces apoptosis, and suppresses cell migration by regulating the AKT, MEK, and PKC/MAPK pathways [ 14 , 15 , 16 , 17 ]. p-Coumaric acid induces cancer cell apoptosis by regulating nuclear damage and repair and apoptosis-related gene expression in MDA-MB-231 cells [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many natural products have also been reported as potential PAK4 inhibitors, including vitexin, emodin, ziganein, and kaempferol ( Arowosegbe et al, 2020 ; Iwaloye et al, 2021 ). However, these compounds generally possess much modest potency against PAK4, and the underlying mechanism needs to be further validated as well.…”
Section: Recent Advances On the Development Of P21-activated Kinase 4...mentioning
confidence: 99%